Impact of Leader Behavior on Employee Experience and Job Satisfaction in Educational Institutions - García-Salirrosas, Elizabeth Emperatriz (2025)
Given the relevance of leadership in the educational environment, there is a need to identify the key elements that influence teacher well-being. Therefore, the present study addresses the impact of leader behavior, specifically initial structure and consideration, on employee experience and job satisfaction in Peruvian educational institutions. The research included a sample of 651 regular basic education teachers in Peru and used a structural equation model using PLS-SEM to evaluate the hypotheses. The following were measured: three dimensions of the employee experience: sensorial, intellectual, and emotional, using validated and reliable instruments. The results indicated that the initial structure positively impacts the three dimensions of the employee experience, while consideration significantly influences the sensorial and emotional experiences but not the intellectual ones. Likewise, it was proven that the three dimensions of the employee experience positively impact job satisfaction. It is concluded that effective leadership, which combines structural clarity and emotional support, improves the work environment and increases staff satisfaction. Finally, implementing leadership training programs is suggested to strengthen these competencies in educational leaders.